Vitamin D receptor as a target for breast cancer therapy. Issue 4 (April 2017) - Murray, Alyson; Madden, Stephen F; Synnott, Naoise C; Klinger, Rut; O'Connor, Darran; O'Donovan, Norma; Gallagher, William; Crown, John; Duffy, Michael J
Abstract : Considerable epidemiological evidence suggests that high levels of circulating vitamin D (VD) are associated with a decreased incidence and increased survival from cancer, i.e., VD may possess anti-cancer properties. The aim of this investigation was therefore to investigate the anti-cancer potential of a low calcaemic vitamin D analogue, i.e., inecalcitol and compare it with the active form of vitamin D, i.e., calcitriol, in a panel of breast cancer cell lines ( n  = 15). Using the MTT assay, IC50 concentrations for response to calcitriol varied from 0.12 µM to >20 µM, whereas those for inecalcitol were significantly lower, ranging from 2.5 nM to 63 nM ( P  = 0.001). Sensitivity to calcitriol and inecalcitol was higher in VD receptor (VDR)-positive compared to VDR-negative cell lines ( P  = 0.0007 and 0.0080, respectively) and in ER-positive compared to ER-negative cell lines ( P  = 0.043 and 0.005, respectively). Using RNA-seq analysis, substantial but not complete overlap was found between genes differentially regulated by calcitriol and inecalcitol. In particular, significantly enriched gene ontology terms such as cell surface signalling and cell communication were found after treatment with inecalcitol but not with calcitriol. In contrast, ossification and bone morphogenesis were found significantly enriched after treatment with calcitriol but not with inecalcitol. Our preclinical results suggest that calcitriol and inecalcitol can inhibit breast cancer cell line growth, especially in cells expressing ER and VDR. As inecalcitol is significantly more potent than calcitriol and has low calcaemic potential, it should be further investigated for the treatment of breast cancer.